Prioritizing Policy Approach and Actions to Address Epidemic of Non Communicable Diseases (NCDs) - Faiz, M Abul; Rahmanb, M Ridwanur; Karim, Md Nazmul (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Not available DOI: http://dx.doi.org/10.3329/jbcps.v30i2.11405 J Bangladesh Coll Phys Surg 2012; 30: 62-64